Electrocardiographic and echocardiographic abnormalities associated with mitral valve prolapse in patients with Marfan syndrome. (25th November 2020) - Lasne, A; Milleron, O; Delorme, G; Arnoult, F; Hanna, N; Arnaud, P; Eliahou, L; Extramiana, F; Iung, B; Boileau, C; Jondeau, G
Abstract: Introduction: Marfan syndrome (MFS) is responsible for cardiovascular disorders such as aortic aneurism and mitral valve prolapse (MVP). A malignant MVP phenotype combining clinical, electrical and morphological features has been described in symptomatic patients who have experienced sudden cardiac death or complex ventricular arrhythmias. We have taken advantage of the high prevalence of MVP in MFS patient to study the clinical, electrical and echocardiographic abnormalities associated with MVP. Purpose: The aim of this study is to describe the clinical, electrical and morphological cardiac abnormalities associated with MVP in a cohort of MFS patients with FBN1 mutations with a high prevalence of MVP and who did not suffer from severe ventricular arrhythmias. Methods: All consecutive patients coming to the National Reference Center for Marfan syndrome were evaluated prospectively i.e. clinical examination, 12-lead electrocardiogram, standard transthoracic echocardiography study and molecular genetic screening. Results: 352 consecutive patients were included from April 2015 to October 2016 [250 FBN1 mutation carriers (MFS) and 102 healthy relatives (HR)]. None of the patients had a history of sudden cardiac death or complex ventricular arrhythmia. MFS vs HR: MFS patients were younger (33 vs 41yo p<0.001) and 2/3 were women in both groups. In the MFS group, abnormal T waves repolarization in lateral leads were more common [172 MFS (70.2%) vs. 87 HR (86.14%) p<0, 0012], as was MVP [38.37% vs 1.96%; p<0, 0001], and diastolic hypertrophy of the basal segment of the inferolateral wall (thickness >11mm) [22.31% vs. 9.18%; p<0.0001]. In MFS, MVP affected either one valve (21.22%), or both (17.14%), and was not associated with electric abnormalities. However, diastolic basal inferolateral wall hypertrophy was associated with mitral valve prolapse (p<0, 0001), QTc interval prolongation (p<0.0229), abnormal T waves repolarization in the inferior leads (p=0.004), and higher aortic Z-Score (p=0.274). Conclusion: In MFS patients, the prevalence of MVP is high and no significant association between MVP and electrical abnormalities was found. In contrast, basal inferolateral wall hypertrophy is associated with MVP and repolarization disorders in inferior leads and QTc interval prolongation, i.e, electrocardiographic abnormalities described in malignant MVP. Funding Acknowledgement: Type of funding source: None